2011
DOI: 10.1007/s10658-011-9888-x
|View full text |Cite
|
Sign up to set email alerts
|

Infection process of Fusarium graminearum in oats (Avena sativa L.)

Abstract: Fusarium head blight in small grain cereals has emerged as a major problem in the Nordic countries. However, the impact of this disease in oats has been less investigated than in other cereals. For this reason we have studied the infection process (the optimal time of infection and infection pathways) of Fusarium graminearum in oats and its subsequent effects on kernel infection, deoxynivalenol (DON) content and germination capacity. In a field experiment the oat cultivar Morton was spray-inoculated at differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 23 publications
2
61
0
Order By: Relevance
“…Crop debris is recognized as a source of F. graminearum inoculum (Pereyra et al 2004). Rainfall is important for conidial dispersal (Xu 2003;Paul et al 2004), thus the positive impact of mean daily precipitation found in our study confirms the importance of spread of the splash dispersed macroconidia (Paul et al 2004;Skelsey and Newton 2015) when the plant is most susceptible to infection (Tekle et al 2012). Rain increases the moisture of crop debris (Manstretta and Rossi 2015) and thus also favours the development of perithecia and maturation of ascospores (Manstretta and Rossi 2016).…”
Section: Association Between Don Content and Weather Conditions At DIsupporting
confidence: 73%
“…Crop debris is recognized as a source of F. graminearum inoculum (Pereyra et al 2004). Rainfall is important for conidial dispersal (Xu 2003;Paul et al 2004), thus the positive impact of mean daily precipitation found in our study confirms the importance of spread of the splash dispersed macroconidia (Paul et al 2004;Skelsey and Newton 2015) when the plant is most susceptible to infection (Tekle et al 2012). Rain increases the moisture of crop debris (Manstretta and Rossi 2015) and thus also favours the development of perithecia and maturation of ascospores (Manstretta and Rossi 2016).…”
Section: Association Between Don Content and Weather Conditions At DIsupporting
confidence: 73%
“…In contrast, weather conditions during heading/flowering seem to have a high influence on the DON-risk in Norwegian oats (Hjelkrem et al 2017). Spray inoculations with F. graminearum at different growth stages have shown that oat is highly susceptible to F. graminearum during flowering (Tekle et al 2012), and positive associations were detected between DON accumulation and rain during the heading/flowering in our previous study (Hjelkrem et al 2017). The negative association detected between HT2 + T2 accumulation in oat grains and rain during the heading/flowering period observed in our Spearman rank correlation study supports the assumption of a different timing of initial i n f e c t i o n b y F. l a n g s e t h i a e c o m p a r e d t o F. graminearum.…”
Section: Discussionmentioning
confidence: 96%
“…By contrast, F. graminearum is considered to infect oat at, or soon after, flowering (Tekle et al 2012), and the risk of DON contamination has been reported to be little influenced by the weather conditions during growth stages prior to flowering (Hjelkrem et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In South America, there is little information available regarding the effects of Fusarium species on the weight of oat grains, although F. graminearum has been reported to be the primary species associated with FHB of small grains such as barley, triticale and wheat. Other Fusarium species such as avenaceum, culmorum, poae, equiseti, acuminatum, trincictum, sambucinum, semitectum and chlamydosporum The damage caused by FHB on cereals can be quantitative and qualitative (Mauler-Machnik & Zahn, 1994;Parry, Jenkinson, & McLeod, 1995;Tekle, Skinnes, & Bjørnstad, 2013), resulting in reduced germination and the production of mycotoxins (Tekle, Skinnes, & Bjørnstad, 2013;Tekle, Dill-Macky, Skinnes, Tronsmo, & Bjørnstad, 2012). Secondary damage can manifest as a reduction in the protein content of the grain (Mauler-Machnik & Zahn, 1994;Mesterházy & Bartok, 1996) and decreased germination and seed vigor (Teckle et al, 2013).…”
Section: Introductionmentioning
confidence: 99%